A systematic review of medial epicondylectomy as a surgical treatment for cubital tunnel syndrome. (November 2017) - O'Grady, Eva E.; Vanat, Qureish; Power, Dominic M.; Tan, Simon
The aim of this study was to review the literature of decompression of the cubital tunnel with medial epicondylectomy and to assess outcomes and complications. Twenty-one case series reported on 886 medial epicondylectomies. The mean percentage of patients obtaining improvement of one or more McGowan grade was 79%. The mean percentage obtaining a good/excellent Wilson Krout grade of outcome was 83%. Of six comparative studies, two showed no significant differences in outcomes between medial epicondylectomy and transposition procedures, and three reported better outcomes with medial epicondylectomy. One reported similar outcomes with medial epicondylectomy and simple decompression. The existing literature on medial epicondylectomy is of limited methodological quality and does not allow for firm conclusions to be drawn regarding its efficacy compared with other surgical techniques. Further studies should aim for high methodological quality, randomized comparison with simple decompression or anterior transposition and should utilize standardized outcome measures. Level of evidence: II